Robustness of the Prediction Filter in Differential Pulse Code Modulation System - Dankovic, Nikola B.; Peric, Zoran H.; Antic, Dragan S.; Peric, Stanisa Lj.; Nikolic, Sasa S. (Elektronika ir Elektrotechnika, 2016)
Robustness of the differential pulse code modulation system with the first and second order predictor is considered in this paper. Special focus is on a robust stability of prediction filter with regard to predictor coefficients. Generalization of robustness in classical sense is performed and suitable relations for calculating probability of robustness are derived. The proposed method for robustness estimation is used for the first and second order prediction filters in the case of speech signal. DOI: http://dx.doi.org/10.5755/j01.eie.22.5.16347